A Review of Research : Exploring Ethnomatematics On Indonesian Traditional Games In Mathematics Learning - Adinda Putri Salsabilah; Aida Ar Rahmah; Ayu Wulandari; Joko Soebagyo (Jurnal Pendidikan Matematika IKIP Veteran Semarang, 2022)
Ethnomathematics is a mathematical concept that exists in a culture. Using ethnomathematics in learning is one of appropriate method. Through learning mathematics that is associated with culture such as traditional games, it create a comfortable learning atmosphere so that students are interested in learning and mathematics seems easy and fun. The positive thing obtained from the concept of ethnomathematics with traditional games is that students can understand the concept and the transfer of values well. This study aims to determine the development of research on ethnomathematics in traditional games. The articles analyzed amounted to 166 of the 370 articles extracted with PoP (Publish or Perish) from the Google Scholar database over a period of 50 years. This research was conducted using bibliometric analysis method using PoP (Publish or Perish) and VOSviewers applications with the keywords "ethnomathematics" and "traditional games". Based on the analysis, it can be concluded that undergraduate and postgraduate and international journals have the most significant influence on citations compared to other journals, which is supported by changes in h-index. The results left 166 articles (a decrease of about 55.13%); data on citations also changed, with 1073 citations (decrease by 86.16%) and 214.60 cites/year (increase by 41.09%). This shows that research on ethnomathematical concepts through traditional games in mathematics learning, is a research topic that has been rising for the past few years based on the increase in citations every year with further exploration this research topic can develop widely and can be another method that can be applied to mathematics learning. Keywords: ethnomathematics, traditional games.